Albumseite mit Zeitungsartikel, Ausstellungsflyer und Fotografien des Iwalewahaus aufgeklebt - Beier, Ulli (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2013)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Newspapers; Exhibitions; Archives; Albums; Newspaper Article; Art Exhibition; Flyer; Iwalewahaus; Cultural Centre